Iluzja i mistyfikacja. O powieściach Andrzeja Barta - Małochleb, Paulina (Śląskie Studia Polonistyczne, 2012)
The article is an analysis of several philosophical-aesthetic categories important for Andrzej Bart’s writing. The subject of interest is the past, history, memory, possibilities of representation and a presentative nature of existence. Bart is shown as an ironist writer, confabulator whose element is a probabilistic history. In his works, he plays with memory consisting in a destabilization of culturally-reinforced images. His characters, on the other hand, participate in life which is most often perceived as a type of mystification. This is a consequence of the conception of reality accepted by the writer. Here, reality is illusoric in nature, forces to taking on different roles and accumulating illusion.